Modeling the depletion of dissolved oxygen in a lake due to submerged macrophytes - Misra, A. K. K. (Nonlinear Analysis: Modelling and Control, 2010)
In this paper a non-linear mathematical model for depletion of dissolved oxygen in a lake due to submerged macrophytes is proposed and analyzed. It is assumed that nutrients are continuously coming to the lake with a constant rate through water run off. In the modeling process five variables are considered, namely concentration of nutrients, density of algal population, density of macrophytes, density of detritus and concentration of dissolved oxygen. Equilibria of the model have been obtained and their stability discussed. The numerical simulation is also performed to support the obtained analytical results.